Penguatan Moderasi Beragama pada Masyarakat Kampung Bintang Pepara - Arda Tonara; Nopri Abadi Miko; Ashari Efendi (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2023)
Life in society has the potential for conflict if moderation in religion is not developed. In 1998, the conflict between the TNI and GAM began in the Bintang Pepara village area. In 2005 the people returned to the Bintang Pepara village. The people of Bintang Pepara village need to be given knowledge about religion, especially religious moderation because the village is located in remote areas. The purpose of this service is to provide understanding to the public about religious moderation. The method used in this service program is the Asset Based Community Development (ABCD) method. Based on the results of community service in Bintang Pepara village, there are five ways to apply the concept of religious moderation in daily life, including: 1) Respecting differences, 2) Increasing understanding, 3) Practicing religious values, 4) Creating dialogue, and 5 ) Maintain a calm demeanor and not be easily provoked.